The Use of Communicative Approach to Improve Local Guide’s Speaking Skill - Anwari, Hamdan - ((JELE) Journal Of English Language and Education, 2020)
This research is to know how the local guides’ speaking skills are after joining the class with a communicative approach and cycles. this  research is categorized into classroom action research. Research employed role play as approach to teaching strategy. There were thirteen local guides as student with different educational background in the class. In conducting research, researcher was accompanied an English teacher as collaborator.  To face learners’ obstacles in speaking English, teachers have to teach using strategy. It tells the technique to teach speaking to the local guides in Kulon Progo with role play as activity in learning process. This research needs two cycles that include five steps such as planning, acting, observing, implementing and reflecting in each cycle. Those cycles shows improvement in speaking English. Learners also show their confident in speaking English in front of their friends. The result of the research is local guides are interested in role play and being confident to speak up. Some speaking aspects are well developed such as pronunciation, grammar, fluency, interactive communication and vocabulary. The pre-test shows score 37.46. It raises to be 40,54 that seen from cycle 1. So that there is improvement of score 3.08. Then, cycle I obtains 40,54 and cycle II obtains 45,925 so that from cycle I to cycle II there is an improvement score 5,385. Meanwhile cycle II and cycle III shows significant improvement score 4,925 from obtained score 45,925 to 50,85. It can be concluded that each cycle shows good improvement. Those scored components are seen from the score and collaborator’s report. The role is interesting in teaching speaking that enhances local guides’ speaking skill